Implementasi Seni Kuda Kincak Gresik sebagai Bahan Ajar IPS Berbasis Etnopedagogi di Sekolah Darar - UMIAD, Siti Mufarrohah; Ganes; Nasution, Nasution; Gunansyah, Ganes; Hendratno, Hendratno; Istiq’faroh, Nurul Istiq’faroh (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research is an effort to implement Kuda Kincak Art as teaching material based on  ethnopedagogy to introduce and strengthen local wisdom values through social studies lessons. The goal is to benefit students by helping them understand and appreciate local cultural heritage while strengthening their social identity. The method used in this research is descriptive qualitative with source triangulation through observation and documentation, as well as method triangulation through Focus Group Discussions (FGD) conducted with 22 fourth-grade students at SDN 129 Gresik during social studies lessons. The data analysis method includes several stages: data reduction, data presentation, conclusion drawing, and data verification. The results of the study show that ethnopedagogy-based social studies learning through Kuda Kincak Art is effective in introducing local wisdom values to students. The learning implementation proved relevant in enhancing students' understanding of cultural, social, and economic values in their community. In conclusion, to deepen knowledge that focuses not only on theory but also on practice, further development is needed through the creation of modules that integrate various learning approaches. Collaboration with the Kuda Kincak art studio and the application of Project-Based Learning (PBL) can help develop practical skills and strengthen students' character in alignment with local wisdom values